Chemical evolution of metamorphic fluids in the Central Alps, Switzerland: insight from LA‐ICPMS analysis of fluid inclusions. Issue 5 (16th September 2016) - Rauchenstein‐Martinek, K.; Wagner, T.; Wälle, M.; Heinrich, C. A.; Arlt, T.
Abstract: The chemical evolution of fluids in Alpine fissure veins (open cavities with large free‐standing crystals) has been studied by combination of fluid inclusion petrography, microthermometry, LA‐ICPMS microanalysis, and thermodynamic modeling. The quartz vein systems cover a metamorphic cross section through the Central Alps (Switzerland), ranging from subgreenschist‐ to amphibolite‐facies conditions. Fluid compositions change from aqueous inclusions in subgreenschist‐ and greenschist‐facies rocks to aqueous–carbonic inclusions in amphibolite‐facies rocks. The fluid composition is constant for each vein, across several fluid inclusion generations that record the growth history of the quartz crystals. Chemical solute geothermometry, fluid inclusion isochores, and constraints from fluid–mineral equilibria modeling were used to reconstruct the pressure–temperature conditions of the Alpine fissure veins and to compare them with the metamorphic path of their host rocks. The data demonstrate that fluids in the Aar massif were trapped close to the metamorphic peak whereas the fluids in the Penninic nappes record early cooling, consistent with retrograde alteration. The good agreement between the fluid–mineral equilibria modeling and observed fluid compositions and host‐rock mineralogy suggests that the fluid inclusions were entrapped under rock‐buffered conditions. The molar Cl/Br ratios of the fluid inclusions are below the seawater value and would require unrealistically high degrees of evaporation and subsequent dilution if they were derived from seawater. The halogen data may thus be better explained by interaction between metamorphic fluids and organic matter or graphite in metasedimentary rocks. The volatile content (CO2, sulfur) in the fluid inclusions increases systematically as function of the metamorphic grade, suggesting that the fluids have been produced by prograde devolatilization reactions. Only the fluids in the highest grade rocks were partly modified by retrograde fluid–rock interactions, and all major element compositions reflect equilibration with the local host rocks during the earliest stages of postmetamorphic uplift.